All Arthroscopic Osteochondral Autograft Transplantation for Medial Talar Dome Lesions Talus With Burring of the Anterior Lip of the Distal Tibia - Maysara Bayomy, M.D.; Mohamed Mosa Mohamed, M.D.; Emad Zayed, M.D.; Ahmed Sayed Esmail, M.D.; Gaber Eid, M.D.; Hossam Elsayed, M.D.; Abdelaziz M. Ali, M.D. (Arthroscopy Techniques, 2024)
Osteochondral lesions of the talus are chondral lesions affecting the subchondral bone mostly due to acute ankle trauma, including either sprains or fractures. After failure of conservative treatment, operative treatment is necessary, with different surgical techniques described in the literature. We describe a single-step osteochondral autograft transfer to access the medial talar dome lesion that avoids the need for a medial malleolar osteotomy and therefore eliminates morbidity while reducing operative time.